Comparison of underlying data structures for distributed ledgers (2019)
Cryptocurrencies, such as Bitcoin, have achieved public recognition in the recent past due to their innovative financial proposal. Such innovation has been deemed a consequence of the blockchain technology underlying said cryptocurrencies. Therefore, this technology is now popularized as an underlying technology for distributed systems, more precisely, for distributed ledgers. However, a look inside cryptocurrencies shows there are still a number of challenges to address for their wide acceptance. These challenges have prompted the proposal of different underlying data structures for distributed ledgers different from the blockchain. The aim of this thesis is to address the optimality of different data structures, by assessing if they can respond to some of the technical challenges identified for this technology and if and how they guarantee its fundamental properties. We conduct a quantitative analysis to compare the data structures with respect to the quality attributes of throughput and latency, and we conduct a qualitative analysis to determine whether they satisfy the fundamental properties. These analyses serve as a basis to conclude which data structures would be more suited for use in different real-life scenarios.